Interpreting top-quark LHC measurements in the standard-model effective field theory - Plehn, Tilman; Russell, Michael; Westhoff, Susanne (Arxiv, 2018)
This note proposes common standards and prescriptions for the effective-field-theory interpretation of top-quark measurements at the LHC.